(4a-5)(4a+5)=

Simple and best practice solution for (4a-5)(4a+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4a-5)(4a+5)= equation:


Simplifying
(4a + -5)(4a + 5) = 0

Reorder the terms:
(-5 + 4a)(4a + 5) = 0

Reorder the terms:
(-5 + 4a)(5 + 4a) = 0

Multiply (-5 + 4a) * (5 + 4a)
(-5(5 + 4a) + 4a * (5 + 4a)) = 0
((5 * -5 + 4a * -5) + 4a * (5 + 4a)) = 0
((-25 + -20a) + 4a * (5 + 4a)) = 0
(-25 + -20a + (5 * 4a + 4a * 4a)) = 0
(-25 + -20a + (20a + 16a2)) = 0

Combine like terms: -20a + 20a = 0
(-25 + 0 + 16a2) = 0
(-25 + 16a2) = 0

Solving
-25 + 16a2 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + 16a2 = 0 + 25

Combine like terms: -25 + 25 = 0
0 + 16a2 = 0 + 25
16a2 = 0 + 25

Combine like terms: 0 + 25 = 25
16a2 = 25

Divide each side by '16'.
a2 = 1.5625

Simplifying
a2 = 1.5625

Take the square root of each side:
a = {-1.25, 1.25}

See similar equations:

| 2x-(x+2)+2x-4=12 | | -4(u-4)=6u+36 | | 3t^4+8t^3+4t^2=0 | | 2m+5n+8m+7n= | | -5u+45=-2(u-9) | | 0.6(x-1)+0.2=6.6 | | -8(y-8)=2y-36 | | 2x-3=4-5x | | (6x^2+8x+12)-(4x^2+3x-2)= | | (3a^2-9a)+(12a^2+5a)= | | 13y-4y=27 | | (2+x)=(x*2) | | 2a+8=7a-5 | | 2.5*2x= | | 0.5x+12.3=7.1-1.1x | | (9x^2+6x+3)+(4x^2-8x+4)= | | 6c^2+21c-4c-14= | | (x+2)2+(y-6)2=25 | | 2x^2+5*2x= | | 3a(5a^2+8a)= | | -5x+7=3x+7 | | 14=6(y-2)+7y | | 6w+2(w+7)=30 | | 25+4y-1=16y-11-5y | | 4x+2y+z=166 | | 3+9x=7x+7-8 | | 5(u-3)-8u=-12 | | 108=LW | | -18n+12=-17n-14 | | A=15*12 | | -3x-10=5x+30 | | (-5xy)(2xy^2)= |

Equations solver categories